Contextual and Fun English Learning for Da’wah Students - Marisa Fran Lina (ELE Reviews: English Language Education Reviews, 2022)
Da’wah Faculty students who become the focus of this study are students majoring in Da’wah Management (DM) who, in the future, will become preachers. It makes them sometimes overlook the benefits of learning English. Learning English will be very important for those who will become important actors in spreading Islamic religion to local and international communities. This research aims to explore contextual and fun English learning for students at Da’wah Faculty at an Islamic University in Indonesia. It explores relevant previous studies and important theories and compares them with this study’s findings. This study employed a descriptive-qualitative approach. The results indicated that DM students studied English according to the context of their knowledge as DM students; and that they studied English in fun ways which could encourage them to be more active in joining the class. These findings help English lecturers to create better learning activities to teach DM students. Meanwhile, further researchers can elaborate more toward the research subjects, so the results will be more varied.